Effect of resistance training on kinetic and kinematic indicators in jump athletes: a systematic review - Rong, Wenchao; Kim, Geok Soh; Samsudin, Shamsulariffin; Zhao, Yue; Wang, Xinzhi; Zhang, Xinrui; Cao, Liang (BioMed Central, 2025)
Background: High, long, and triple jumps are athletic jumping events. Although they differ in technique and rules, they share many similar biomechanical characteristics. Resistance training is a key method for enhancing jumping performance and has gained attention. Different resistance training methods have been shown to significantly improve jumping performance. However, current research on these events remains insufficient, particularly in systematically analysing kinetic and kinematic indicators, exploring their relationships, and summarising common characteristics, which are crucial. These gaps hinder a deeper understanding of how resistance training affects jumping performance. Objective: To explore the relationship between kinetic and kinematic indicators, examining how resistance training influences force conversion into momentum, optimises body movement coordination, and enhances take-off performance in jumping events. Results: The quality assessment results showed that four randomised controlled trials (RCTs) were evaluated using the ROB-2 tool. Among them, two studies raised concerns about bias related to the randomisation process, and one study also exhibited bias due to deviations from the intended interventions. Five non-randomised intervention studies were assessed using the ROBINS-I tool, with two studies judged to have a moderate risk of bias due to confounding factors. Overall, five studies were identified as having a moderate risk of bias or raising concerns in specific areas. Kinematic indicators (e.g., squat jump, countermovement jump, high jump height, standing long jump, and standing triple jump) showed significant improvements. Jump height significantly improved (SMD = 0.99; 95% CI = 0.56–1.41, P < 0.0001), and jump distance improved significantly (SMD = 1.67; 95% CI = 0.93–2.40, P < 0.0001). Conclusion: This review examines the significant effects of resistance training on kinetic and kinematic indicators of jumping performance, emphasizing its critical role in enhancing athletic performance. Resistance training significantly improves explosive power, take-off force, and maximal strength, particularly through exercises like squat jumps, which are closely linked to enhanced jump performance. Additionally, neuromuscular adaptations stabilize the output of antagonist muscles, further supporting performance enhancement. In terms of kinematic indicators, resistance training enhances jump height and distance, with methods such as plyometric and barbell jump training proving especially effective. These methods are beneficial for elite athletes and those with some training experience. However, the research highlights that gender and athletic level influence training outcomes, with females generally showing less improvement. The review also underscores the need for more high-quality randomized controlled trials (RCTs) to validate these findings further, as most current studies rely on non-randomized controlled trials (non-RCTs). Systematic review registration: https://www.crd.york.ac.uk/prospero, Identifier: CRD42025628838.